YouTube, Children, and Collaborative Culture. A Literature Review - Tur-Viñes, Victoria; Núñez-Gómez, Patricia; Martínez-Pastor, Esther (Historia y Comunicación Social, 2019)
The purpose of this paper is to identify empirical insights through a summary of the evidence-based knowledge on young youtubers. Taking a participatory culture perspective, a systematic review has been conducted of 65 academic papers published since 2008. The article condenses existing findings on young youtubers practices, motivation for using YouTube, type of YouTube content, and parental intermediation, as well as legal, regulatory, and educational aspects in need of attention. Also addressed are the marketing strategies used by brands on YouTube and their effects on young audiences. The implications of the young youtuber phenomenon are considered, as well as necessary lines of future research.